Contents and Values of Ho Chi Minh’s thought on Human Rights - Tha, Ha Trong (International Journal of Psychosocial Rehabilitation, 2020)
President Ho Chi Minh (1890 -1969) was a hero of national liberation and a great man of culture of Vietnam. He was one of the first great people of the 20th century to contribute greatly to solving issues of human rights. His whole life was devoted to class liberation, national liberation and human liberation. The paper aims to clarify contents of Ho Chi Minh’s thought on human rights, which stem from traditional values of Vietnamese people and universal values of humanity regarding human rights in the context of the world and Vietnam from late 19th to mid-20th century, especially from the urgent need for human rights of a country that had fell victim to slavery like Vietnam at that time, which led it to have profound and unique features. From which, the paper presents values of Ho Chi Minh’s thought on human rights in terms of theory and practice, especially in the current period.